FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KECEMASAN PASIEN POST OPERASI TUR (TRANS URETRA RESECTION) DENGAN SPINAL ANESTESI DI RUANG INAP MAWAR II DAN MAWAR III RSUD DR. MOEWARDI SURAKARTA - Hasanudin, Muh; Maliya, Arina (Jurnal Berita Ilmu Keperawatan, 2009)
Background of Study. The surgery action are healing of disease by cutting of slicing organ. One of the effect from surgery is patient dread after experiencing operation. The factors are influence dread of TUR operation post patient consist of internal factors (food needed, elimination, family factor) and external factors (medical equipments, drug, health energy attitude, compliance of patient at regulation). The research aims. This research aims to know the factors are medical equipments, drug, health energy attitude, compliance of patient at regulation related to level dread of post patient operate for TUR with anesthesia spinal in RSUD DR. Moewardi Surakarta. Research Method. This Research represent quantitative research, non experiment, designed by used are descriptive of correlation that are research meaning to look for correlation among two free variable factors and variable tied. While used by research device is sectional cross because free variable data collecting and variable tied to be conducted during at the same time at one time. Population at this research are all post patient operate for TUR in Space Take Care Of To lodge Rose II and Rose III RSUD DR. Moewardi Surakarta with amount of research sample 35 patient. Conclusions. Data analysis at this research is bivariate. To be able to test and analyze data used is technique of Chi-Square. Result of research show (1) there are correlation which are significant use of medical equipments to storey; level dread [of] patient (Ï‡2= 9,087; p = 0,002), (2) there are relation which significant medicines to storey; level dread of patient (Ï‡2 = 8,077; p = 0,004), (3) there are relation between health energy attitude significant to storey ;level dread [of] patient ((Ï‡2 = 9,087; p = 0,002), and (4) there are relation compliance of patient at regulation to storey; level dread of patient (Ï‡2 = 9,087; p = 0,002).